Essentials of Sleep Medicine A Practical Approach to Patients with Sleep Complaints - Badr, M. Safwan; Martin, Jennifer L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Humana, 2022)
This book provides an overview of sleep and sleep disorders for practicing clinicians. Sleep disorders represent a major portion of the chief complaints seen by pulmonologists and other clinicians. Patients with sleep-related conditions often present with non-specific complaints that require a broad and detailed knowledge of the wide range of sleep disorders and their consequences. This concise, evidence-based review of sleep medicine offers a guide to pulmonologists, primary care physicians, and all clinicians involved in caring for patients with sleep disorders. Providing a focused, scientific basis for the effects of sleep on human physiology, especially cardiac and respiratory physiology, chapters also outline a differential diagnosis for common sleep complaints and an evidence-based approach to diagnosis and management. This includes a review of the current standards of practice and of emerging technology and unresolved issues awaiting further research. In all, this book provides a clear diagnostic and management program for all the different sleep disorders and includes key points and summaries. This new edition expands the scope of the previous to include additional sleep disorders and the most affected populations. Six new chapters are added on health disparities in sleep medicine, models of care for patients with sleep disorders/care coordination, sleep disordered breathing in pediatric populations, sleep in hospitalized patients, sleep in pregnancy, and sleep in older patients. Essentials of Sleep Medicine is an invaluable resource for physicians, clinical psychologists, respiratory care practitioners, polysomnographic technologists, graduate students, clinical researchers, and other health professionals seeking an in-depth review of sleep medicine.
SECTION I: INTRODUCTION TO SLEEP MEDICINE -- Normal human sleep -- Pharmacology of Sleep -- Health disparities in sleep medicine -- Models of care for patients with sleep disorders/care coordination -- Cases -- SECTION II: SLEEP DISORDERED BREATHING -- Sleep Disordered Breathing: Epidemiology and clinical presentation -- Sleep Disordered Breathing: Diagnosis -- Obstructive Sleep Apnea: Pathophysiology and Clinical management (treatments) -- Central Sleep Apnea: Pathophysiology and clinical management -- Hypoventilation during sleep -- Peri-operative care for patients with obstructive sleep apnea -- SDB in pediatric populations -- Cases -- SECTION III: OTHER SLEEP DISORDERS -- Diagnosis of insomnia disorder -- Treatment of insomnia (CBT-I and pharmacotherapy) -- Circadian Rhythm Sleep Wake Phase Disorders -- Narcolepsy -- Parasomnias -- Movement disorders -- Sleep in critical illness -- Sleep in hospitalized patients -- Sleep in pregnancy -- Sleep in older patients -- Cases.
Keywords: Internal medicine; Primary care (Medicine).; Internal Medicine; Primary Care Medicine; Sleep Apnea Syndromes; Sleep Wake Disorders; Sleep -- physiology